The Key Influencers Of Mainland Degree Student Satisfaction In Taiwan: Two Years After The First Enrolment - Rudakowska, Anna (Penerbit Universiti Sains Malaysia (USM Press), 2014)
In the year 2011, Taiwan for the first time opened its higher education to degree students from Mainland China. However, the number of applicants who took advantage of this policy in the first two years after implementation was much below Taipei government expectations. Given the growing importance of the overseas students to generate additional revenue for higher education, as well as the development of people-to-people contact across the Taiwan Strait, the goal of this article is to spot the main challenges that Taiwanese universities and policymakers face in attracting more Mainland students. This research gleans information from the Mainland students' point of view through a survey conducted at thirteen Taiwanese universities nationwide. It applies a methodology called the Net Promoter Score (NPS), which grants respondents the freedom to express their opinions, perceptions and reflections without limitations set by the interviewer's perspective. This research has found that satisfaction of the Mainland degree students studying in Taiwan is mainly driven by a distinctive learning environment, as they appreciate the "free," "relaxed" and "open" atmosphere at Taiwanese universities. Secondly, the students highly prize opportunities for personal and professional development, and thirdly, they enjoy Taiwanese friendliness and culture and particularly appreciate the nurturing of traditions. However, these positives are offset by negative factors perceived by the students. Mainland degree students feel strong resentment towards the inequality and discrimination they face. There are two sources of this problem. The first is the guidelines established by the Taiwanese government regulating the stay of Mainland students. Those rules are described as detrimental to the future career development and therefore discriminatory. The second is the negative perception and attitude felt among Taiwanese towards people from the People's Republic of China (PRC). These factors are responsible for a very high percentage of dissatisfied degree students (41 percent) who are most likely to discourage their friends and relatives from studying in Taiwan in comparison with the relatively small percentage of extremely satisfied students (23 percent), who are very likely to actively encourage their compatriots to study in Taiwan.